2017
DOI: 10.1190/geo2015-0167.1
|View full text |Cite
|
Sign up to set email alerts
|

Converted-wave seismic imaging: Amplitude-balancing source-independent imaging conditions

Abstract: We have developed crosscorrelational and deconvolutional forms of a source-independent converted-wave imaging condition (SICW-IC) and show the relationship between them using a concept of conversion ratio coefficient, a concept that we developed through reflection, transmission, and conversion coefficients. We applied the SICW-ICs to a two half-space model and the synthetic Marmousi I and II models and show the sensitivity of the SICW-ICs to incorrect wave speed models. We also compare the SICW-ICs and source-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In principle, using different types of wave phases (e.g. primary and converted-waves) is possible to map the discontinuity interface, which has been demonstrated by several authors (Nihei et al 2000;Xiao & Schuster 2009;Shang et al 2012;Shabelansky et al 2017). This is because the fracture serving as secondary sources can generate converted waves when primary waves pass through the fracture.…”
Section: Converted-wave Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, using different types of wave phases (e.g. primary and converted-waves) is possible to map the discontinuity interface, which has been demonstrated by several authors (Nihei et al 2000;Xiao & Schuster 2009;Shang et al 2012;Shabelansky et al 2017). This is because the fracture serving as secondary sources can generate converted waves when primary waves pass through the fracture.…”
Section: Converted-wave Effectsmentioning
confidence: 99%
“…Recent development of using the interference between different types of wave phases (Nihei et al 2000;Xiao & Schuster 2009;Shang et al 2012;Shabelansky et al 2017) may give us another solution. However, all those imaging approaches involving processing converted S-wave pose restrictions to demand not only P-wave velocity model but also S-wave velocity model which is rarely available for imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Shang et al (2012) and Shabelansky et al (2015) argued that passive seismic without location information can be used to achieve the source-free subsurface image. Based on the relationship between the P-wavefield and converted S-wavefield in the receiver extrapolation, Shabelansky et al (2017) demonstrated a source-free converted-wave RTM imaging condition, which only uses the back-propagation Pand S-waves to perform cross-correlation imaging. As a result, it does not require source extrapolation, thereby saving In this study, we apply the vector imaging condition to the RTM of the first-order velocity-dilatation-rotation elastic wave equations.…”
Section: Imaging Conditionmentioning
confidence: 99%
“…Then, based on the idea of vector dot product cross-correlation, we present a more precise source-free P-SV converted-wave imaging condition. Shabelansky et al (2017) gave a source-free converted-wave imaging condition:…”
Section: Imaging Conditionmentioning
confidence: 99%
“…Following the same idea, Shabelansky et al (2015) developed a velocity analysis method using reflection/transmission waves and converted waves using both active and passive seismic data. Shabelansky et al (2017) further elaborated the source-independent converted wave imaging condition for better amplitude balancing with the deconvolutional forms.…”
Section: Introductionmentioning
confidence: 99%